(untitled) (Research, Society and Development, 2020)
In order to detect patterns of rural vegetation in the coastal region of the Pampa Biome, a floristic survey of a natural pasture located on the Southern Coastal Plain in Rio Grande do Sul, in the buffer zone of the Ecological Reserve of Taim (32 ° 32’03.27 S” and 52 ° 31’43.98 ”O), was conducted. The evaluations were carried out by in frames 0,25m² to estimate the botanical composition and the Daubenmeire scale was used to assess plants coverage. Aiming to detect possible patterns of vegetation variation in a Entisols Quartzipsamments, sandy texture, flat relief, lake and marine sediment substrate, the sample units were distributed in order to characterize three visually contrasting conditions: I - higher relief, with greater drainage and high proportion of bare soil (> 30%); II - intermediate relief, medium drainage and medium proportion of uncovered soil (10 to 20%); III.- lower relief, higher humidity and lower proportion of uncovered soil (<10%). 66 0.25m² frames were used, distributed in the three conditions. A total of 18 species were recorded in six families. The specie with the greatest coverage was Axonopus parodii regardless of soil condition, since Paspalum pumilum was only found in condition III, indicating its high dependence on greater water availability. All species in the hot season are perennial while all hibernal species are annual, and of these, Poa annua shows a strong tendency to greater coverage with increased soil moisture.